Combinatorial Effects of Crude Plant Extracts of Murraya koeniggi And Selected Antibiotics on Methicillin-Resistant Staphylococcal Species - Himashi, Imanda Gurudeniya (2017)
Antibiotic resistance is an alarming phenomenon worldwide, challenging the effectiveness of antibiotics which are used to treat mankind. One of the recommended ways to treat antibiotic resistance is combinatorial therapy which combines crude medicinal plant extracts and standard antibiotics. The pure cultures of nine different MRSA (methicillin-resistant Staphyloccous epidermidis) , two Staphylococcus aureus and two Staphylococcus epidermidis isolates were obtained from INTI International University culture collection. The combinatorial effect of curry leaves (Murraya koenigii) extracts (aqueous, ethanolic, methanolic) and standard antibiotics amplicillin and gentamicin were examined against selected MRSA and MRSE strains. Thesusceptibility of curry leaf extracts alone, antibiotics alone and in combination against MRSA and MRSE were observed using the agar well diffusion method. Water, ethanol and methanol wereused as negative controls in the respective plates and each experiment was done in triplicates. In this study, methanolic extract exhibited better antimicrobial effect on MRSA and MRSE compared to aqueous and ethanolic extracts. One of the MRSA strains (N12) was resistant to gentamicin but was resistant to ampicillin and did not exhibit any susceptibility to the combination of gentamicin and M. koenigii. All S. epidermidis isolates were resistant to ampilicillin and did not exhibit and susceptibility to the methanolic extracts, alone or combination with antibiotics. In conclusion, there is a possible combinatorial effect affect exhibited by M. koenigii and gentamicin m in MRSA isolates to gentamicin, but this has to be tested with a larger number of bacterial isolate, including MRSA.